2020
DOI: 10.1063/5.0011756
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical study of diethylmethylammonium methanesulfonate under anhydrous conditions

Abstract: The protic ionic liquid diethylmethylammonium methanesulfonate ([DEMA][OMs]) was analyzed in depth by differential scanning calorimetry (DSC), nuclear magnetic resonance (NMR) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, 2 Raman spectroscopy and broadband dielectric spectroscopy (BDS) under anhydrous conditions. Karl Fischer titration, NMR and FT-IR spectra confirmed the high purity of [DEMA][OMs]. The melting point (37.7 °C) and the freezing point (14.0 °C) obtained by DSC agree well with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…It was shown that the obtained melting point ( T m = 283.6 K with Δ m H = 9.78 kJ·mol –1 ) is in good agreement with the literature value reported by Nakamoto and Watanabe . The melting point is significantly lower than the value reported by Pan et al (310.85 K) . It is worth adding that the water content in the methanesulfonate-based IL tested in this work is high as presented in Table .…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…It was shown that the obtained melting point ( T m = 283.6 K with Δ m H = 9.78 kJ·mol –1 ) is in good agreement with the literature value reported by Nakamoto and Watanabe . The melting point is significantly lower than the value reported by Pan et al (310.85 K) . It is worth adding that the water content in the methanesulfonate-based IL tested in this work is high as presented in Table .…”
Section: Methodssupporting
confidence: 89%
“…Because Nakamoto and Watanabe do not show water content in [N H,1,2,2 ]­[CH 3 SO 3 ], there is no certainty whether the declared melting point applies to a pure compound. In addition, the melting point published by Pan et al for this IL is definitely higher, which results from a lower water content. Despite this, this temperature is also difficult to consider as the temperature of a pure IL as the authors declare a water content of 7000 ppm.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…To study σ dc in terms of energy landscape for the related temperature range, the activation energies in phase I and the melt phase are calculated based on eqn (6) , which can be obtained by performing partial differentiation of eqn (3) in its logarithmic form with respect to T ( eqn (5) ). 41,46,47 E a = RT 2 (∂ln σ / ∂T ) E a = RBT 2 /( T − T V ) 2 − RT /2 …”
Section: Resultsmentioning
confidence: 99%
“…The system was then cooled down to 293 K. Afterwards, the sample was heated up again to 413 K with temperature interval of 1 K. The detailed operation process can be found in ref. 41 .…”
Section: Methodsmentioning
confidence: 99%